2017
DOI: 10.1515/jeb-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Unemployed Workers’ Perceptions of Stress and Employment Prospects in Macedonia: The Role of Alternative Adjustment Mechanisms

Abstract: Depressed labour market conditions in Macedonia manifested by high and persistent unemployment rate, strong segmentation and prevailing long-term unemployment is considered as a heritage of more than two decades long period of transition. Unemployment has a number of negative consequences such a decreased income which is assumed to influence the subjective experience of unemployment. The negative macroeconomic shocks in Macedonia have been mitigated due to the strengthened role of alternative labour market adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…In this context, alternative adjustment mechanisms have emerged in less developed transition countries alongside traditional forms of adjustment. These alternatives include mechanisms such as employment in the informal sector, inactivity and emigration (Nikoloski and Pechijareski 2017).…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, alternative adjustment mechanisms have emerged in less developed transition countries alongside traditional forms of adjustment. These alternatives include mechanisms such as employment in the informal sector, inactivity and emigration (Nikoloski and Pechijareski 2017).…”
Section: Research Contextmentioning
confidence: 99%
“…In this context, previous studies have found that people living alone and lone parents, as well as families with dependent children, are especially vulnerable to material deprivation (Boarini and Mira d'Ercole 2006). Here it might be that intra-household transfers play an important role in maintaining the well-being of the household: namely, in deprived households with one or more unemployed members, income from various sources can be distributed among all members of the household in order to satisfy basic needs (Nikoloski and Pechijareski 2017).…”
Section: Figure 1 -Severe Materials Deprivation Rates Eu-silc (2015)mentioning
confidence: 99%
“…The same conclusion regarding the importance of income pooling and inter-household transfers holds in this case as well when it comes to alleviation of poverty within the household. In this context, the role of inter-household transfers has been already identified with respect to alleviation of perceived level of stress among unemployed (Nikoloski and Pechijareski, 2017). Being unemployed in a single adult household would increase the probability of poverty by more than 2.5 times, whereas the social benefits significantly reduce this probability.…”
Section: Empirical Analysismentioning
confidence: 99%
“…El desempleo conlleva efectos físicos, sociales y psicológicos que varían dependiendo de factores como el contexto social y económico, la personalidad y el sexo (Caballero, 2015;Navarro, Climent, López y Gómez, 2018). Diversos estudios han demostrado que las personas desempleadas manifiestan niveles mayores de estrés percibido, ansiedad y depresión, y que el desempleo afecta de forma negativa la percepción de bienestar (Nikoloski y Pechijareski, 2017). El estrés se genera cuando la persona percibe que su entorno o una situación particular sobrepasa sus recursos personales y pone en riesgo su bienestar; de acuerdo con la evaluación cognitiva que hace de la situación, puede hacer uso de sus capacidades de afrontamiento del estrés, que son aquellos esfuerzos cognitivos y conductuales que se desarrollan para dar una respuesta a las demandas que exceden los recursos personales (Lazarus y Folkman, 1985).…”
Section: Introductionunclassified